OPTIMALISASI TUGAS CAMAT DALAM MENGKOORDINASI KEGIATAN PEMBERDAYAAN MASYARAKAT DI KECAMATAN LARANGAN KOTA TANGERANG - Kamaludin Kamaludin; Doddy Mulyono (Bussman Journal : Indonesian Journal of Business and Management, 2023)
In this study, there was a sample of 104 people, consisting of the sub-district head, the sub-district secretary, the head of the empowerment section, 3 village heads and 98 people from the Larangan sub-district community. The sampling technique used for the community uses the purpose sampling method, namely determining the sample with certain considerations because the number is large and adjusted to the research objectives. For sub-district heads, sub-district secretaries and heads of community empowerment sections, the census collection technique was used. The data collection technique used in this research was primary data collected by filling out questionnaires and interviews, while secondary data was obtained by observation. In analyzing the researcher used table tools. Based on the analysis carried out by the researchers, it can be concluded that the Optimization of the Subdistrict Head's Duties in Coordinating Community Empowerment Activities in Larangan District, Tangerang City has been considered quite good. To further increase community participation in carrying out community empowerment activities, the sub-district should conduct training for the community to provide input and knowledge, so that the community has the ability to participate in empowerment programs carried out by the sub-district, so that it can produce quality human resources